Superaerophilic Materials Are Surprising Catalysts: Wettability-Induced Excellent Hydrogenation Activity under Ambient H2 Pressure - Li, Z.; Cao, C.; Zhu, Z.; Liu, Jian; Song, W.; Jiang, L. (Wiley-VCH Verlag, 2018)
© 2018 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim Liquid hydrogenation reaction is one of the essential reactions in fine chemical and pharmaceutical industry. The low H2 concentration on catalyst surface is a major kinetic limitation for these reactions. In this study, it is proposed and demonstrated for the first time that creating superaerophilic surface is an efficient way to increase H2 concentration on catalyst surface, and thus significantly enhancing the hydrogenation reaction rate in aqueous solution. As a proof of concept, Pd nanoparticles loaded on graphene aerogel (GA) with different degrees of aerophilic/aerophobic surfaces (denoted as Pd/GA, Pd/NGA-2, and Pd/NGA-4, respectively) are prepared and tested for hydrogenation reactions. Pd/GA with superaerophilic property (H2 bursting time within 92 ms) shows the highest catalytic reaction rate in all tested reactions under the same conditions, including hydrogenation of styrene, nitro, and aldehyde compounds. The hydrogenation of aldehyde compounds with Pd/GA at ambient H2 pressure is even comparable to those of Pd/NGA-4 and commercial Pd/C with superaerophobic property at 6 bar H2 pressure. Such strategy is expected to find wide applications in many other catalytic reactions involving gases, and may lead to revolutionary change in fine chemical industry.